Pengembangan Booklet Pencemaran Lingkungan Berbasis Potensi Lokal di MAS YP Haji Datuk Abdullah - Santri, Ratih Nimas; Sudibyo, Mufti (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research aims to Know the level of feasibility teacher response, student’s response and effectiveness of learning resources in the form of Environmental Pollution Booklets based on Local Potential based on material experts, learning experts and design experts. The type of research that will be carried out in this study is development research (Research and Development). This research is focused on developing booklet learning media based on local potential on Environmental Pollution material. The development model used is the 4D model (Define, Design, Development, and Disseminate). The data collection techniques used in this research are interviews, observations, questionnaires or questionnaires and tests. The research results show that the local potential-based environmental pollution booklet learning media that has been developed is declared “Very Feasible” based on the assessment of material experts with the category “Very Feasible” (89.13%), based on learning experts with the category “Very Feasible” (93.18), and based on design experts with the category “Very Feasible” (90, 78%), the results of the effectiveness of the good category which means that the local potential-based booklet developed is effective in improving student learning outcomes, namely there is a difference between pretest and posttest scores with an average pretest score of 54.22 while the average posttest score is 84.06 with an average N-Gain value of 0.64.